First-order-reversal-curve analysis of rare earth permanent magnet nanostructures: insight into the coercivity enhancement mechanism through regulating the Nd-rich phase. Issue 8 (27th November 2020) - Xu, Junjie; Zhu, Kai; Li, Wei; Wang, Xiaobai; Yang, Ziyu; Hou, Yanglong; Gao, Song
Abstract : The coercivity enhancement mechanism of Nd2 Fe14 B-based nanostructures with Nd-rich phase is revealed by first-order-reversal-curve diagram, which is that increased Nd-rich phase content leads to optimized magnetic interactions and microstructure. Abstract : Rare earth permanent magnet nanostructures have attracted intensive interest recently due to the increasing demand for integrated and miniaturized devices. As a typical example, hard magnetic Nd2 Fe14 B-based nanostructures with desired coercivity have been developed by a reduction–diffusion process and the Nd-rich phase is supposed to be essential to optimize the magnetic properties, whereas the identification and role of the Nd-rich phase have not been addressed so far. Herein, Nd2 Fe14 B-based nanostructures with different Nd-rich phase contents, Nd15 Fe77 B8 and Nd14.2 Fe78.6 B7.2, are rationally prepared by a reduction–diffusion process. The coercivity of Nd15 Fe77 B8 can reach 5 kOe, which is higher than that of Nd14.2 Fe78.6 B7.2 of 3.2 kOe. First-order-reversal-curve (FORC) analysis confirms the amorphous paramagnetic Nd-rich phase as pinning centers and reveals magnetic interactions and magnetic domain nature in the two nanostructures. The increase of the Nd-rich phase optimizes microstructures and magnetic interactions, responsible for higher coercivity. This work points out the relationship between the Nd-rich phase, magnetic interactions, microstructures, and magnetic properties, and could usher in new ways of fabricating advanced permanent magnetic nanostructures.